Model performance in estimating the yield of common bean cultivars1 Desempenho de modelos na estimativa da produtividade de cultivares de feijoeiro - Filla, Vinicius Augusto [UNESP]; Coelho, Anderson Prates [UNESP]; Bettiol, Joao Victor Trombeta [UNESP]; Leal, Fabio Tiraboschi [UNESP]; Lemos, Leandro Borges [UNESP]; Rosalen, David Luciano [UNESP] (Univ Federal Ceara, Dept Geol, 2023)
The use of vegetation indices has good potential for predicting the productivity of several crops, but factors such as the time of assessment, cultivar, and plant phenology can influence the performance of predictive models. The objective of this study was to evaluate and compare the precision of estimating the common bean grain yield, according to the normalized difference vegetation index (NDVI), using individual models per cultivar and a general model with all cultivars. The cultivars IAC Imperador and IPR Campos Gerais, with determined and indeterminate growth habits, respectively, were evaluated. They were subjected to different nitrogen management methods to provide grain yield variability. NDVI evaluations were conducted throughout the culture cycle on six dates during the vegetative and reproductive stages. The common bean grain yield was estimated with high precision as a function of NDVI, obtaining a precision of up to 78% and an average error close to 350 kg ha-1. The greatest fit of estimation was obtained in the phenological reproductive stages of beans, especially after crop flowering. General models, composed of data from more than one cultivar, had similar precision and, in some cases, superiority to the fitted models for each cultivar, demonstrating the feasibility of using the same model for several genotypes.
Keywords: NDVI; Phaseolus vulgaris L; Remote sensing; Vegetation index